Conduct Problem Trajectories Between Age 4 and 17 and Their Association with Behavioral Adjustment in Emerging Adulthood - Sentse, Miranda; Kretschmer, Tina; de Haan, Amaranta; Prinzie, Peter (Journal of Youth and Adolescence, 2017)
Individual heterogeneity exists in the onset and development of conduct problems, but theoretical claims about predictors and prognosis are often not consistent with the empirical findings. This study examined shape and outcomes of conduct problem trajectories in a Belgian population-based sample (N = 682; 49.5 % boys). Mothers reported on children’s conduct problems across six waves (age 4–17) and emerging adults reported on their behavioral adjustment (age 17–20). Applying mixture modeling, we found four gender-invariant trajectories (labeled life-course-persistent, adolescence-onset, childhood-limited, and low). The life-course-persistent group was least favorably adjusted, but the adolescence-onset group was similarly maladjusted in externalizing problems and may be less normative (15 % of the sample) than previously believed. The childhood-limited group was at heightened risk for specifically internalizing problems, being more worrisome than its label suggests. Interventions should not only be aimed at early detection of conduct problems, but also at adolescents to avoid future maladjustment.
CRIS-Team Scopus Importer:2025-03-19
Keywords: Antisocial behavior; Conduct problems; Emerging adulthood; Mixture modeling; Trajectories